A synthesis of hornwort diversity: Patterns, causes and future work - Villarreal, J. C.; Cargill, D. C.; Hagborg, A.; Soderstrom, L.; Renzaglia, K. S. (Phytotaxa, 2014)
Hornworts are the least species-rich bryophyte group, with around 200-250 species worldwide. Despite their low species numbers, hornworts represent a key group for understanding the evolution of plant form because the best-sampled current phylogenies place them as sister to the tracheophytes. Despite their low taxonomic diversity, the group has not been monographed worldwide. There are few well-documented hornwort floras for temperate or tropical areas. Moreover, no species level phylogenies or population studies are available for hornworts. Here we aim at filling some important gaps in hornwort biology and biodiversity. We provide estimates of hornwort species richness worldwide, identifying centers of diversity. We also present two examples of the impact of recent work in elucidating the composition and circumscription of the genera Megaceros and Nothoceros. Important areas for further research are highlighted, particularly at taxonomic, ultrastructural, phylogenetic and genomic levels.